Rheological inversion in high-grade metamorphic rocks: Evidence from folds, inverse folds, mullions and boudins (Bohemian Massif) - Zulauf, Gernold; Finger, Fritz; Gerdes, Axel; Müller, Wolfgang; Tholen, Sören; Žák, Jiří (Journal of structural geology, 2025)
We investigated the effects of Variscan deformation on Cadomian metagranitoids and intercalated mafic sheets (amphibolite and mafic gneiss) in the Moldanubian and Moravo-Silesian units of the southeastern Bohemian Massif. Given the contrasting mechanical strength of felsic and mafic minerals, deformation is expected to be accommodated by folding and/or boudinage of the competent mafic sheets within the incompetent granitoid host. However, the studied examples show a competence inversion indicated by (1) a stronger foliation in the mafic sheets, (2) extension-parallel mullions at shortened contacts and inverse folds at extended contacts with the cusps pointing into the felsic rock, and (3) extension-parallel folding and boudinage of felsic veins within amphibolite matrix. The lobate phase boundaries in mafic and felsic rocks suggest that the competence inversion was related to a switch in the dominant deformation mechanism from dislocation to phase-boundary diffusion creep in the stability field of high-quartz (T > 650 °C). As phase-boundary diffusion is enhanced by a decreasing grain size, the fine-grained mafic rocks behaved mechanically weaker than the coarser grained felsic rocks. This inversion in viscosity occurred at ca. 332 Ma (U-Pb on titanite) and might have been also supported by the basal slip of biotite within the mafic sheets. •Mafic dikes are mechanically weaker than felsic host.•Strain rate is controlled by the grain size of main phases.•Phase-boundary diffusion results in rheological inversion.•Extension-parallel mullions coeval with inverse folds.•Extension-parallel folds coeval with boudins.